Dormência de sementes e manejo de Solanum americanum Mill. - Forte, César Tiago (2019)
Blackbird (Solanum americanum Mill.) is a weed species in the Solanaceae family. It has wide distribution in the Brazilian territory, competing with the main crops of economic interest, both winter and summer. Knowledge of the intrinsic characteristics of weed species is justified by the development of specific control strategies, minimizing production costs and environmental impact. The objective of this work was to evaluate the effect of different chemical agents to overcome the dormancy of S. americanum seeds, as well as the behavior of the species before herbicide application. The works were divided into two phases, in the first one the study focused on obtaining the best chemical method to overcome dormancy of blackbird seeds. In the second phase experiments were carried out with the objective of obtaining knowledge about the real situation of the resistance level of S. americanum to the main herbicides used for its management and the behavior of the species with the application in different stages and doses of glyphosate. In relation to the first phase, there was no increase in germination with washing of S. americanum seeds. The concentration of 0.84 g L-1 for gibberellic acid (AG3) and the exposure time of 21.22 h in potassium nitrate (KNO3) at 0.2% showed the maximum technical efficiency in seed germination from S. americanum. For sowing depth and mulching effect germination occurs when seeds remain on the soil surface and without the presence of mulch. Regarding the possible resistance, the herbicides iodosulfuron and metsulfuron-methyl (inhibitors of enzyme ALS), applied postemergence, do not control the species S. americanum. This species has no resistance to glyphosate herbicide, however, changes may be occurring, which may result in resistant genotypes. When applied at the 5-leaf stage, 25% (180 g e.a ha-1 ) of the recommended glyphosate dose is sufficient for S. americanum not to produce offspring.